Coloring Assistance for Increasing Creativity of TPQ Nurul Qoryah's Children - Tira Nur Fitria (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2022)
This community service activity assists/trains coloring to increase the creativity of TPQ Nurul Qoryah's children. This community service method uses the simulation/demonstration method. This activity is implemented on Saturday, 4 June 2022, and involves 25 children. The process of assistance/training activities is carried out by 1) providing image media (coloring paper). 2) introducing colors. Children can choose and mention colors from existing colored pencils/crayons. 3) direct children to give the right colors according to the picture. It shows that children can choose colors according to the picture's color even though there are still many visible shortcomings, such as a mixture of colors that do not fit the image and many colors that cross the lines in the picture. 4) giving rewards to children. This reward has a positive impact on further activities. It shows that most children could select and identify colors from the available colored pencils. Children can color drawings as a consequence of the training process, even though deficiencies must be addressed, such as a mixture of colors that did not match the image and many colors that crossed the image's lines. The activity was carried out smoothly from the beginning to the end. All the children were enthusiastic during the assistance. From assistance (training) activities, several benefits and obstacles are faced. The benefits are 1) practice handwriting, 2) relaxation, and patience. 3) practice focusing and concentrating. 4) increase knowledge. 5) improve motoric skills. 6) stimulates creativity. 7) express expression and feelings. While the obstacles are assistance/training, media facilities are still lacking. 2) facing the unstable spirit of children. 3) relatively little time where the time used is from 15.30-17.00 WIB. To minimize the activity, the required time is at least two hours in each stage of the assistance/training